Long-Term Quality of Life of Kidney Transplant Recipients - Kimura, Renata Namie Yoshioka (2024)
Introduction: The relevance of quality of life is increasingly evident in rising life expectancy and the prevalence of noncommunicable chronic diseases like chronic kidney disease. Transplantation is the preferred treatment for end-stage chronic kidney disease, facilitated through living or cadaveric donors as per Brazilian legislation. However, limited literature compares long-term quality of life data and its correlation with graft origin. This study addresses this knowledge gap, focusing on patients who underwent kidney transplantation before 2012 at Hospital Universitário Evangélico Mackenzie. Objectives: The primary aim is to analyze kidney transplant recipients’ long-term quality of life from living and cadaveric donors. Methods: The study was observational cross-sectional; the sample includes 24 female (61.5% cadaveric donor) and 19 male (38.5% cadaveric donor) patients who underwent transplantation before 2012. The Short Form-36 (SF-36) questionnaire was utilized, and data were statistically analyzed after tabulation in Excel®. Results: Cadaveric donor recipients experienced 39 additional months of dialysis (p = 0.017) and higher initial median creatinine levels than living donor recipients. Creatinine findings were morefavorable for living donor recipients in the 7th and 8th years, indicating a temporal decline in the cadaveric donor group. In the SF-36 questionnaire, only the “mental health” domain showed a statistically significant difference, favoring the cadaveric donor group (p = 0.008). Conclusion: Long-term quality of life for living donor and cadaveric donor kidney transplant recipients did not significantly differ, except for the “mental health” domain, which favored cadaveric donor recipients. Creatinine levels exhibited a temporal decline in the cadaveric donor group, emphasizing the importance of considering graft origin in assessing transplant outcomes.